Validation of Moticon`s OpenGo sensor insoles during gait, jumps, balance and cross-country skiing specific imitation movements - Stöggl, T.; Martiner, A. (Journal of Sports Sciences, 2017)
Abstract: The purpose of this study was the experimental validation of the OpenGo sensor insole system compared to PedarX sensor insole and AMTI force-plate systems. Sixteen healthy participants performed trials in walking, running, jumping (drop and counter movement jumps), imitation drills and balance, with simultaneous measures of all three systems. Detected ground contact and flight times with OpenGo during walking, running and jumping were similar to those of AMTI. Force-time curves revealed comparable shapes between all three systems. Force impulses were 13-34% lower with OpenGo when compared to AMTI. Despite differences in mean values in some exercise modes, correlations towards AMTI were between r = 0.8 and r = 1.0 in most situations. During fast motions, with high force and impact, OpenGo provided lower force and latency in force kinetics. During balance tasks, discrepancy in the centre of pressure was found medio-lateral, while anterio-posterior direction was closer to AMTI. With awareness of these limitations, OpenGo can be applied in both clinical and research settings to evaluate temporal, force and balance parameters during different types of motion. The fully mobile OpenGo system allows for the easy and quick system application, analysis and feedback under complex field conditions, as well.